Pelatihan jaringan komputer dan keamanannya bagi dosen dan mahasiswa Dili Institute of Technology (DIT) di Undika Surabaya - Slamet Slamet (Universitas Pendidikan Indonesia (UPI), 2023)
The Dili Institute of Technology (DIT) is a non-profit, community-based educational organization that focuses on meeting the higher education and vocational training needs of young people, veterans of the resistance, and the children of veterans. It is dedicated to providing general education and training that will help the country become more technically and commercially skilled, creating a workforce that can satisfy the needs of the corporate, public, and community sectors in Timor Leste. Its mission is to provide high-quality education and training based on international standards at undergraduate and postgraduate levels, and in professional training. To prepare students to obtain good qualifications and professions that are adequate to meet constraints, especially those related to network management skills and security measures. Class lecturers and computer laboratory assistants only know the theory of using computers, but lack advanced skills about networks and security to teach students. To deal with this problem, it is necessary to provide understanding and practice to DIT lecturers and students regarding computer networks and their security. The preparation of activities is carried out directly in a participatory manner so that lecturers and students can understand and implement the use of computer networks and their security. The result is training and understanding of network fundamentals for lecturers to transfer their skills to students, while students can deepen their knowledge in the field of networks and security systems. Practical skills in implementing this security using special devices from Cisco and Mikrotik.